2019
DOI: 10.1038/s41398-019-0459-9
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of exosomes in mental disorders

Abstract: Exosomes are a class of extracellular vesicles of endocytic origin, which are released by cells and are accessible in biofluids, such as saliva, urine, and plasma. These vesicles are enriched with small RNA, and they play a role in many physiological processes. In the brain, they are involved in processes including synaptic plasticity, neuronal stress response, cell-to-cell communication and neurogenesis. While exosomes have been implicated previously in cancer and neurodegenerative diseases, research regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
243
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(262 citation statements)
references
References 98 publications
2
243
0
Order By: Relevance
“…Moreover, radio-and chemotherapy may also influence the development of treatment-resistant cancer cells [75], possibly through cellular reprogramming [109] and/or the formation of brain metastasis [110]. Genetics [54,111], age [71], existing comorbidities [112,113], lifestyle [114,115], and environmental [116] factors are likely to alter the extracellular fate of exosomes, which leads to CRCI (Figure 2). Changes in exosomal cargo content and their release may further influence diverse mechanisms/pathways capable of impacting the brain and CNS function, which could result in CRCI (Figure 3).…”
Section: Mechanisms Associated With Exosomes and Crcimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, radio-and chemotherapy may also influence the development of treatment-resistant cancer cells [75], possibly through cellular reprogramming [109] and/or the formation of brain metastasis [110]. Genetics [54,111], age [71], existing comorbidities [112,113], lifestyle [114,115], and environmental [116] factors are likely to alter the extracellular fate of exosomes, which leads to CRCI (Figure 2). Changes in exosomal cargo content and their release may further influence diverse mechanisms/pathways capable of impacting the brain and CNS function, which could result in CRCI (Figure 3).…”
Section: Mechanisms Associated With Exosomes and Crcimentioning
confidence: 99%
“…Although the precise mechanisms underlying CRCI remain to be established, several studies suggest there is a link between exosomes and CRCI. Exosome biogenesis, its cargo content, function, and activity may be influenced by cancer [97], cancer therapies [93,102], genetics [54,111], age [71], existing comorbidities [112,113], lifestyle [114,115], and environmental [116] factors. Differences in exosomal content (e.g., miRNAs and proteins) and release may exert protective or damaging effects that could alter the brain and CNS function, and cause declining cognitive health in cancer survivors.…”
Section: Potential Implication Of Exosomes In Crci Researchmentioning
confidence: 99%
“…Interestingly, it has been recently shown that inflammatory stimuli are able to modify the miRNA cargo of miR-125a-5p and miR-16-5p in glial sEVs to decrease the dendritic complexity of developing hippocampal neurons [8]. New exciting and growing evidence claims for a role of exosome-like vesicles in mental disorders [80].…”
Section: Astrocyte-derived Sevs In Neurological Conditionsmentioning
confidence: 99%
“…Exosomes are naturally occurring biological nanoparticles, with their size usually defined in the range from ∼30 nm up to 100 nm or sometimes up to 200 nm . Other types of extracellular vesicles (EVs) include microvesicles (50–1,000 nm, which bud directly off the plasma membrane), ectosomes (vesicles assembled at and released from a plasma membrane), shedding vesicles, microparticles and apoptotic vesicles (500–2,000 nm, which bud off the membrane of cells undergoing apoptosis) . In another paper, extracellular vesicles were divided into distinct subpopulations based on their size: 90–120 nm (large exosomes), 60–80 nm (small exosomes) and 35 nm (non‐membranous particles called exomeres) (Figure ).…”
Section: Exosomesmentioning
confidence: 99%
“…Circulating myocardial microRNAs carried by exosomes are responsible for the cross‐talk between ischemic heart and bone marrow and thereby make possible the systemic response to cardiac injury required for cardiac repair and circulating microRNAs were involved in signalling causing pre‐term birth in mice . Since exosomes can carry cargo across the blood‐brain barrier and they lack an immune response, they play an important role in the development and progression of neurodegenerative and mental diseases, as well as in neurophysiological processes . Moreover, enhanced penetration through the blood brain barrier was achieved by the coating of gold nanoparticles (NPs) by neuron‐targeted exosomes …”
Section: Exosomesmentioning
confidence: 99%